The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.14710/jitaa.34.3.223-228
|View full text |Cite
|
Sign up to set email alerts
|

DIET COMPOSITION OF ANOA (Buballus sp.) STUDIED USING DIRECT OBSERVATION AND DUNG ANALYSIS METHOD IN THEIR HABITAT

Abstract: Anoa are fully protected under Indonesian Law since 1931 (Law of Protection of Wild Animals 1931, no 134). Increasing law enforcement regarding hunting as well as promoting awareness of the Anoas unique threatened the existence of conservation measures. The modern concept of conservation based on the sustainability utilization, and therefore the knowledge of the Anoa preference in feeding to support the sustainability conservation should be studied. In the present study, the combination of direct observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…Digestibility will increase if the feedstuffs containing low crude fiber. This result was in line with Pujaningsih et al (2009) which concluded by the research's result that feed digestibility depend on undigestible fat content.…”
Section: Dry and Organic Matter Digestibilitysupporting
confidence: 92%
“…Digestibility will increase if the feedstuffs containing low crude fiber. This result was in line with Pujaningsih et al (2009) which concluded by the research's result that feed digestibility depend on undigestible fat content.…”
Section: Dry and Organic Matter Digestibilitysupporting
confidence: 92%
“…Hasil yang sama ditemukan dari penelitian Imran (2008) yang menyebutkan anoa dataran rendah lebih banyak memakan daun maupun buah hampir 93%. Sedangkan hasil penelitian Pujianingsih et al (2009) menunjukkan anoa memakan daun dan buah sebesar 24% sisanya 18% berupa bunga, 12% buah, tunas 8%, rumput dan umbi sebesar 4% serta lumut 2%. Anoa termasuk ke dalam kelompok satwa liar besar (umumnya mempunyai berat tubuh yang dapat mencapai lebih dari 15 kg) (Alikodra, 2010).…”
Section: A Identifikasi Jenis Tumbuhan Pakanunclassified
“…Anoa will be more aggressive during the lust [8]. When a male anoa meets a female, there will be a fight so the process of mating will be difficult to be happen [9]. The female Anoa will be willing to accept the male while experiencing the peak of the estrus that occurred only a few hours.…”
Section: Introductionmentioning
confidence: 99%